Hidden pathologies of maxillary sinus using CBCT scans - Md Sanaullah; Abhishek Sinha; Sunita Srivastava; Anuj Mishra; Yakshi Singh; Shalini Basu (Wolters Kluwer Medknow Publications, 2021)
Introduction: Diagnosis of orofacial pathologies is difficult with the 2 dimensional (2D) images taken from conventional radiography. Cone-beam computed tomography (CBCT) has been developed with 3 dimensional (3D) modalities and has become a better alternative to conventional radiography. Highre solution axial, coronal, and sagittal sections are the most revealing, noninvasive techniques for assessing the maxillary sinus anatomical variations, pathology, and its adjacent structures and areas. Aim: This study aimed to analyze the prevalence of pathological changes in the maxillary sinus of asymptomatic cases using CBCT for diagnostic purposes. Materials and Methods: This study was evaluated among 200 patients for hidden pathologies in the maxillary sinus. Pathological findings were categorized as a mucosal thickening, polypoid mucosal thickening, radiopacification, and no pathological findings. Results: In the present study, the overall prevalence of the mucous retention cyst was found to be 30.25%, the polyp was 4.25%, the mucocele was 0.50%, and the overall mucosal thickenings was 35%. Conclusions: In our study, the mucosal thickening has a very high rate of incidental maxillary sinus pathologies in asymptomatic patients. Therefore, a detailed three-dimensional imaging using CBCT is stated in most patients for proper treatment planning. A careful review of the entire CBCT scans is essential to avoid under-or overestimation of potential complications in providing comprehensive health care.